(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research is intended to examine acute toxicity of untreated water in Labeo rohita. A 96-hour acute toxicity test to measure the LC50 of 5 concentrations of untreated sewage water was undertaken, namely, 10, 25, 50, 70 and 100. Results of the research demonstrate that in less than 24 hours, 100 percent of the fingerlings exposed to a concentration of untreated sewage water had a mortality rate. The exposure of the fingerlings to 10, 25 and 50 UT likewise exhibited substantial (p < 0.05) development in the 96-hour timeframe. The research therefore found that untreated sewage water in Labeo rohita may have acute harmful effects, which need the treatment of waste water before it is released into water bodies.